CRISPR/Cas9 RNP-assisted validation of palmarumycin biosynthetic gene cluster in Lophiotrema sp. F6932 - Gakuubi, Martin Muthee; Ching, Kuan Chieh; Munusamy, Madhaiyan; Wibowo, Mario; Lim, Chun Teck; Ma, Guang-Lei; Liang, Zhao-Xun; Kanagasundaram, Yoganathan; Ng, Siew Bee (Frontiers in Microbiology, 2022)
Lophiotrema is a genus of ascomycetous fungi within the family Lophiotremataceae. Members of this genus have been isolated as endophytes from a wide range of host plants and also from plant debris within terrestrial and marine habitats, where they are thought to function as saprobes. Lophiotrema sp. F6932 was isolated from white mangrove (Avicennia officinalis) in Pulau Ubin Island, Singapore. Crude extracts from the fungus exhibited strong antibacterial activity, and bioassay-guided isolation and structure elucidation of bioactive constituents led to the isolation of palmarumycin C8 and its new analogue palmarumycin CP30. Whole genome sequencing analysis resulted in the identification of a putative type 1 iterative PKS (PAL) predicated to be involved in the biosynthesis of palmarumycins. To verify the involvement of PAL in the biosynthesis of these compounds, we employed ribonucleoprotein (RNP)-mediated CRISPR-Cas9 to induce targeted deletion of the ketosynthase (KS) domain in PAL. Double strand breaks (DSBs) upstream and downstream of the KS domain was followed by homology directed repair (HDR) with a hygromycin resistance cassette flanked by a 50 bp of homology on both sides of the DSBs. The resultant deletion mutants displayed completely different phenotypes compared to the wild-type strain, as they had different colony morphology and were no longer able to produce palmarumycins or melanin. This study therefore, confirms the involvement of PAL in the biosynthesis of palmarumycins, and paves the way for implementing similar approach in the characterization of other gene clusters of interest in this largely understudied fungal strain